2019
DOI: 10.1111/bjet.12772
|View full text |Cite
|
Sign up to set email alerts
|

Social scholarship revisited: Changing scholarly practices in the age of social media

Abstract: Christine Greenhow is an associate professor in Educational Psychology & Educational Technology, Michigan State University. She studies various forms of learning with social media, the design of social-mediated environments for learning and changes in scholarship practices with new media. (More information at: http://www.cgreenhow.org and @chrisgreenhow on Twitter). Benjamin Gleason is an assistant professor in the School of Education, Iowa State University. His research interests include teaching and learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 73 publications
2
34
0
1
Order By: Relevance
“…Today, critical considerations of the professional development of education scholars are situated within larger discussions regarding access to knowledge, the preparation of public intellectuals, and research access and transparency through social, digital, open or networked participatory scholarship (Greenhow & Gleason, , ; Greenhow et al , ; Pearce et al , ; Selwyn, ; Veletsianos, ). This study focused on one group of educational researchers and observed their practices over two brief time periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, critical considerations of the professional development of education scholars are situated within larger discussions regarding access to knowledge, the preparation of public intellectuals, and research access and transparency through social, digital, open or networked participatory scholarship (Greenhow & Gleason, , ; Greenhow et al , ; Pearce et al , ; Selwyn, ; Veletsianos, ). This study focused on one group of educational researchers and observed their practices over two brief time periods.…”
Section: Discussionmentioning
confidence: 99%
“……when utilizing a digital backchannel, the conversation, communications and commentaries are disrupted across a non-cohesive network in which the recipients are constantly changing…traditional conversation structures are missing from the Twitter corpus, resulting in a different type of participatory culture; rather than following interactions in an ordered exchange, users are placed in a multidirectional discursive space…note taking activity provides an essential mediator in the co-construction of meaning within the conference and to the wider …community of practice… encouraging a more participatory conference culture. (Ross et al, 2011, p. 235) Implications for research and practice Today, critical considerations of the professional development of education scholars are situated within larger discussions regarding access to knowledge, the preparation of public intellectuals, and research access and transparency through social, digital, open or networked participatory scholarship (Greenhow & Gleason, 2014Greenhow et al, 2019;Pearce et al, 2010;Selwyn, 2011;Veletsianos, 2016). This study focused on one group of educational researchers and observed their practices over two brief time periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In my study, I define social media as "web-based services that allow individuals, communities, and organizations to collaborate, connect, interact, and build community by enabling them to create, co-create, modify, share, and engage with user-generated content that is easily accessible" (McCay-Peet & Quan-Haase, 2017, p. 17). Importantly for my study, Greenhow et al (2019) note that "online social networks [can] facilitate new ways of creating, manipulating, representing and distributing knowledge" in HE (p. 988). These new forms of knowledge production are the principal focus of my study, especially in terms of the interplay of technology, politics and values woven into such knowledge production.…”
Section: Social Media Academic Libraries and Higher Educationmentioning
confidence: 99%
“…No studies in the library-practitioner literature, however, frame librarians' Twitter practices as producers of knowledge. This is curious given that, as discussed above, TEL theorists note that social media constitutes a burgeoning area of knowledge production in HE (Greenhow et al, 2019;Lang & Lemon, 2014). The library-practitioner literature, moreover, widely argues that contemporary academic libraries, in addition to being for the storage and retrieval of information and educating users about information literacy, are creators of knowledge, particularly in the area of research support (Dempsey, 2017).…”
Section: Social Media Academic Libraries and Higher Educationmentioning
confidence: 99%